Semiotic Analysis of The Film "Dua Garis Biru" By Gina S. Noer - Kurniawan, Mohammad Anas; Najmussalim, Muhammad Hadri; Divan, Tengku Fikri Alamsyah; Kuncoroyakti, Yohanes Arie (Persepsi: Communication Journal, 2025)
The purpose of this study is to analyze semiotic signs in the film Dua Garis Biru referring to the semiotic approach according to Roland Barthes. The reason for choosing this film is because it raises complex social issues regarding teenage pregnancy, family conflict, and social pressure in modern Indonesian society. This study applies a qualitative descriptive method using a two-level semiotic analysis technique according to Barthes: denotation and connotation. The results of the analysis show that this film contains many visual symbols and dialogues that are full of meaning, representing the social reality of teenagers and the role of the family. Symbols such as the blue line, the dining table, and the classroom are the main elements in communicating moral messages and cultural aspects. Through the interpretation of these signs, this film is able to arouse the audience's social awareness of the importance of sex education, communication in the family, and adolescent responsibility.